2022
DOI: 10.3892/or.2022.8455
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin‑leucine arginine promotes colorectal cancer cell proliferation by activating the PI3K/Akt/Wnt/β‑catenin pathway

Abstract: Microcystin-leucine arginine (MC-LR) is an environmental toxin produced by cyanobacteria and is considered to be a potent carcinogen. However, to the best of our knowledge, the effect of MC-LR on colorectal cancer (CRC) cell proliferation has never been studied. The aim of the present study was to investigate the effect of MC-LR on CRC cell proliferation and the underlying mechanisms. Firstly, a Cell Counting Kit-8 (CCK-8) assay was conducted to determine cell viability at different concentrations, and 50 nM M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(65 reference statements)
2
4
0
Order By: Relevance
“…3 D). These findings align with prior research demonstrating that β-catenin and its downstream molecules, including Cyclin D1, are upregulated in colorectal cancer cells treated with MC-LR [ 23 ]. Increased levels of Cyclin D1 and β-catenin proteins have been linked to unfavorable survival outcomes in cancer patients, and Cyclin D1 is known to play crucial roles in cancer development and progression [ 65 , 66 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…3 D). These findings align with prior research demonstrating that β-catenin and its downstream molecules, including Cyclin D1, are upregulated in colorectal cancer cells treated with MC-LR [ 23 ]. Increased levels of Cyclin D1 and β-catenin proteins have been linked to unfavorable survival outcomes in cancer patients, and Cyclin D1 is known to play crucial roles in cancer development and progression [ 65 , 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…The concentrations of MC-LR employed in our study are comparable to those found in microcystin-polluted surface waters, typically below 100 μg/L (equivalent to approximately 100.5 nM) [ 29 ]. MC-LR is recognized for its dual impact on cells, eliciting cell death at high concentrations (>10 μM) [ 48 , 49 ] and promoting cell proliferation at lower concentrations (<500 nM) [ 23 , 30 , 32 ]. In our study, we found that 10 nM and 100 nM MC-LR stimulated cell division and migration in CCA and cholangiocytes cells at certain concentrations (10 nM and 100 nM) but not at lower (1 nM) or higher (1000 nM) concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, β-Catenin is unable to translocate to the nucleus and stimulate the expression of downstream target genes involved in cancerous phenotypes. The PI3K/Akt and Wnt/β-Catenin pathways are activated in several types of cancers 33 . The abnormal activation of the Akt/GSK3β/β-Catenin signaling pathway plays a key role in cancerous progress 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%